Numerical studies of the dynamic behaviour of sandwich plates initially weakened by the impact damage - Burlayenko, Vyacheslav. N.; Sadowski, Tomasz (Left Grupa, Poland, 2009)
Free vibrations of impact-damaged sandwich plates with honeycomb and foam cores are studied. It is assumed that damages caused by impact events are to exist before the vibration start and to be constant during oscillations. The influence of the impact damage modes involving the core crushing (planar damage), face sheets fracture (indentation) and the core to face sheets interface degradation (debonding) on the natural frequencies and associated mode shapes of the sandwich plates is investigated using commercially available finite element code ABAQUSᵀᴹ.